Foreign Direct Investment, Official Development Assistance and Economic Growth effect on Human Development in Selected Asian countries - Wasif Anis,; Humaira Ali,; Dr. Muhammad Aurangzeb Khan,; Raheela Begum,; Khalida,; Abdul Jabbar, (Al-Qanṭara, 2022)
Human development implies expanding people's choices, improving their abilities, and improving their opportunities. Asian countries are concentrating their efforts on raising living standards and promoting human development. This study is an effort to highlight the factors affecting or improving human development in selected Asian countries. The findings of this research demonstrate that foreign direct investment, urban population, trade openness, and economic growth are the key factors that enhance human development in these selected Asian countries. It is suggested that strategy formulation in Asian economies should implement and endorse more human development in these countries which will helps in achieving high economic growth. There should be a useful and transparent utilization of foreign aid for human development. Moreover, there must be stability in the economy to attract more foreign direct investment in these countries. Keywords: FDI, ODA, GDP, HDI